2020
DOI: 10.3390/nu12020426
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Inflammatory Food Consumption and Age-Related Hearing Loss in a Prospective Observational Cohort: Results from the Salus in Apulia Study

Abstract: Age related hearing loss (ARHL) affects about one third of the elderly population. It is suggested that the senescence of the hair cells could be modulated by inflammation. Thus, intake of anti- and pro-inflammatory foods is of high interest. Methods: From the MICOL study population, 734 participants were selected that participated in the 2013 to 2018 examination including hearing ability and from which past data collected in 2005/2008 was available. ARHL status was determined and compared cross-sectionally an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 69 publications
1
40
0
1
Order By: Relevance
“…Seeds and nuts, fruits, and seaweed have considered anti-inflammatory food ingredients [ 38 , 44 , 45 , 46 ]. There is growing acceptance that inflammation could play a role in ARHL [ 16 , 19 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seeds and nuts, fruits, and seaweed have considered anti-inflammatory food ingredients [ 38 , 44 , 45 , 46 ]. There is growing acceptance that inflammation could play a role in ARHL [ 16 , 19 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results suggest that consuming anti-inflammatory foods could be important for ameliorating ARHL. However, an observational cohort study found that pro-inflammatory foods like sugars and alcohol were associated with ARHL, but not anti-inflammatory foods [ 38 ]. Contrary to previous studies, our data found that higher consumption of seeds and nuts, fruits, and seaweed were positively associated with better PTAs at 4FA and HF, but not pro-inflammatory foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that C-reactive protein, a systemic inflammation marker, is increased in current smokers compared to ex-smokers and those who have never smoked 36 , 37 . Moreover, a recent study has suggested that inflammatory food consumption is closely related to the incidence of ARHL 38 . Given that chronic inflammation increases the risk of cardiovascular events, as supported by the results of the JUPITER trial, smoking and diabetes may cause vascular pathologies, such as atherosclerosis 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Our research included individuals from the Salus in Apulia Study (previous Great Age Study), an ongoing population-based prospective cohort comprising of 2472 individuals aged 65 years old or older and residents in Castellana Grotte, a town located near Bari, Puglia, in the southeast of Italy. The Salus in Apulia Study (Great Age Study) focused on the sequence of lifestyle including diet, frailty, and other age-related impairments and age-related disease outcomes [ 28 , 29 ]. The Institutional Review Board of the National Institute of Gastroenterology “S.…”
Section: Methodsmentioning
confidence: 99%